REVENUE SHARING CONCERNING GENERAL, SPECIAL ALLOCATION FUNDS, AND AUTONOMY FOR CAPITAL EXPENDITURES ABOUT ECONOMIC GROWTH - Mahesa Vicky Satria Ramdhan Lihu; Umar Effendi; Candra Kusuma Negara (Jurnal Ekonomi, 2022)
This study aims to ascertain and analyze whether the Profit Sharing Fund, General Allocation Fund, Special Allocation Fund, and Special Autonomy Fund have a simultaneous and limited impact on capital expenditure on district/city governments in South Kalimantan Province. It also seeks to ascertain and analyze whether the Economic Growth variable, which serves as a coding variable, can strengthen or weaken the influence of the Profit Sharing Fund, General Allocation Fund, Special Allocation Fund, and Special Autonomy Fund. The study's findings demonstrated that capital expenditure was significantly impacted by the Profit Sharing Fund, General Allocation Fund, Special Allocation Fund, and Special Autonomy Fund. Part of the capital expenditures are not considerably affected by the profit sharing fund but significantly impacted by the general allocation fund, not dramatically affected by the special allocation fund, and significantly impacted by the special autonomy fund. The influence of the Profit Sharing Fund, the General Allocation Fund, the Special Allocation Fund, and the Special Autonomy Fund on Capital Expenditure cannot be moderated by the Economic Growth Variable.